Genetic variants associated with sudden cardiac death in the young: a systematic review - Ghadeer M. M. Abdelaal; Shaimaa A. Shehata; Shrouk Mohamed Ali; Dena Mohamed Naguib Abdel Moawed (Egyptian Journal of Forensic Sciences)
Abstract Background Sudden cardiac death (SCD) in young individuals is a devastating event with significant genetic contributions. This systematic review comprehensively assesses the association between genetic variants and increased SCD risk in individuals under 35 years. A systematic search of PubMed, Scopus, and Web of Science databases was conducted following PRISMA guidelines using relevant keywords. Main body The review identified 21 studies. Most studies reported a higher proportion of males. Reviewed studies demonstrated a significant association between specific genetic variants and increased SCD risk. Common variants associated with SCD included those in genes encoding cardiac ion channels (e.g., SCN5A, KCNQ1, KCNH2, RYR2), calmodulin (CALM2), sarcomeric proteins (TNN, MYH7, TNNI3, MYBPC3), and desmosomal proteins (PKP2, DSC2). These variants encompass various types, including single nucleotide polymorphisms (SNPs), indels, splicing variants, and copy number variations, with missense mutations being the most prevalent. Such variants can disrupt cardiac electrical and structural integrity, leading to life-threatening arrhythmias. These variants are frequently implicated in inherited cardiac conditions such as hypertrophic cardiomyopathy, dilated cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, long QT syndrome, Brugada syndrome, catecholaminergic polymorphic ventricular tachycardia, and short QT syndrome. Furthermore, multifactorial genetic contributions to SCD in the young were identified in the context of arrhythmias associated with sudden infant death syndrome, mitral valve prolapse, congenital heart defects, and epilepsy, underscoring a shared genetic basis. While the prevalence and clinical significance of these variants varied across studies, their consistent association with SCD highlights the critical role of genetic factors in SCD pathogenesis. Conclusions This review provides evidence that specific genetic variants are associated with an increased risk of SCD in young individuals. These findings highlight the importance of genetic screening and early intervention in individuals with a family history of SCD or risk factors for inherited cardiac conditions. Further research is needed to refine risk prediction models and develop effective prevention and management strategies for SCD in this population.